Improving Students’ Collaboration and Creativity In Learning Procedure Text Writing Through Project-based Learning - Agustin Pratiwi; Ikhsanudin Ikhsanudin; Dwi Riyanti (Jurnal Riset dan Inovasi Pembelajaran, 2026)
Collaboration and creativity are essential skills in modern education, however students at SMK Taruna Muhammadiyah Mempawah faced problem in both areas. Based on the preliminary study, only two group members were actively working on the writing task, while the others remained passive and distracting. Their creativity was also limited, as they only copied the examples given by the teacher instead of generating original ideas. This study aims to improve students' collaboration and creativity in learning procedure text writing through Project-Based Learning (PjBL). Conducted from July to August 2024 at SMK Taruna Muhammadiyah Mempawah, this study involved 18 students of grade XI and used a classroom action research. Data were collected through observation, documentation, and interviews and analyzed in three stages: data reduction, data presentation, and verification. The results show that Project-Based Learning (PjBL) significantly improved students’ collaboration and creativity in writing procedure texts. In Cycle 1, most students worked individually, shared only simple ideas, and produced basic steps with no revisions or editing, resulting in unclear and incomplete texts. In Cycle 2, students became more active in discussions, contributed ideas more equally, and worked together during drafting, revising, and editing. This stronger collaboration helped students generate more detailed, useful, and creative instructions, such as adding safety tips, clearer explanations, and problem-solving steps. Creativity also improved as students began exploring alternative techniques and refining their writing with better vocabulary and organization. Overall, the increase in collaboration supported the rise in creativity, showing that PjBL effectively encouraged teamwork, deeper thinking, and more meaningful writing development.